The Determinant of Job Performance for Laborers in Manufacturing Companies in Jakarta - Juwita*, Ratna; Wulandari, Karina; Arifa, Adinda Delia; Hakim, Arif Rahman; Rabbani, Muhammad Umar; Tambunan, Ryan Andreas; Ardiansyah, Sahril (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This study aims to answer the determinants of job performance based on workplace spirituality, workplace climate, and compensation. Spiritual workplaces are represented by engaging work and a sense of community. By conducting multiple regression tests on respondents from manufacturing companies in Jakarta, it can be concluded that a sense of community and compensation determine the increase in the job performance of workers. The method used is descriptive and verification tests with the classical assumption test. To increase the sense of community, companies can emphasize the formation of workers' sense of belonging to an organization through informal activities such as outings and 'small talks' with employees so that they feel part of the company. Keywords: Job Performance; Workplace Spirituality; Workplace Climate; Compensation; Engaging Work; Sense of Community